2017
DOI: 10.1111/jocd.12389
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic dermatology and emotional well‐being according to gender

Abstract: People who are familiar with Aesthetic Dermatology and have a better attitude toward it, are also more self-confident, more optimistic and more motivated; with emotional strength. Regarding gender, it is expected that women may seek more consultation and esthetic dermatology treatments than men do.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The services included are facial, manicure, pedicure and depilation treatments. Therefore, it can be seen through the rapid growth of beauty centers [3] and an increasing number of cosmetologists venturing into this field are very important for today's society in fulfilling the demands of mental health, psychological needs, or health and beauty treatment [6], [7]. The beauty centers are also associated with the purpose of the community visiting them is to enhance their appearance and personal wellbeing [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The services included are facial, manicure, pedicure and depilation treatments. Therefore, it can be seen through the rapid growth of beauty centers [3] and an increasing number of cosmetologists venturing into this field are very important for today's society in fulfilling the demands of mental health, psychological needs, or health and beauty treatment [6], [7]. The beauty centers are also associated with the purpose of the community visiting them is to enhance their appearance and personal wellbeing [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is parallel with a study [14], where the great services provided by the cosmetology students can increase customer loyalty to visit their favorite beauty centers. Furthermore, effective beauty treatment and consultation services also help to improve the quality of life and psychological needs [3], [6], [83] as well as being able to meet the customer's mental health demands [84]. The use of training modules in T&L will increase the knowledge of HBP in the field they are involved [85].…”
mentioning
confidence: 99%
“…DEBIE was performed in 770 Spanish adults for two dimensions, that is, emotional well‐being and perception of AD. A statistically significant and directly proportional relationship has been found between the degree of emotional well‐being (self‐esteem, assertiveness, optimism, and motivation) and the knowledge about AD and their attitude toward AD (Martínez‐González, Martínez‐González, & Guerra‐Tapia, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 It has been shown that cosmetic interventions may improve patients' quality of life (QoL); however, they require comprehensive patient education and objective information. [3][4][5][6] We created a text-based patient-information-chatbot named 'Beautybot' covering themes such as wrinkles and pigmentation disorders. Written and image-based content was provided in a multiple-choice-driven algorithmic workflow.…”
mentioning
confidence: 99%